Investigating the Moral, Social, Economic, Cultural and Political Rights of Women and the Family in the Human Rights Charter (Islamic Scholarship with Secular Science in the Eyes of the Woman) - Zahra Mosavi; Tayebeh Mahrosadeh; Mohammad Seyfi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study is to review and criticize the human rights charter in the social, economic, cultural, and political component of women and family in relation to the religion of Islam. The research method is objective and fundamental in terms of collecting data in the research class. The data were collected using a snippet, library, and document method. After analyzing the research data, the qualitative content analysis method resulted in the following results. In terms of content, some UN programs and documents, the relationship with women's rights and the strengthening of the foundation of the family, as well as the recognition of women's fundamental rights and freedoms, have been attempted, but in the eyes of United Nations agencies, the rights of women and the family are often the ones that need to be investigated. In this article, the damage Ethics in the areas of the right to life, the right to liberty, the right to work, the right to education, the right to protection and so on, minimum social, civil, and political rights of women and children were extracted, and the moral model of human rights in the component of women's and family rights was based on Islamic principles. In the end, the result was that the way to cure and to escape the moral harm arising from the human rights charter and women's rights conventions that are themselves based on secular, humanistic and communist views is Islamic and ethical.